ประชาธิปไตยกับพฤติกรรมเลียนแบบด้านการใช้ความรุนแรงในสภา - โพธิ์หวังประสิทธิ์, ไพบูลย์ (JOURNAL OF SOUTHERN TECHNOLOGY, 2013)
ปรากฏการณ์การใช้ความรุนแรงในสภาทั้งที่เกิดขึ้นในประเทศต่าง ๆ ทั่วโลกและสภาของไทย สามารถมองในมุมหนึ่งได้ว่าเป็นพฤติกรรมเลียนแบบด้านการใช้ความรุนแรง ดังนั้นบทความนี้จึงมีวัตถุประสงค์เพื่อทบทวนความหมายและหลักการสำคัญของประชาธิปไตย โดยเฉพาะอย่างยิ่งประชาธิปไตยแบบรัฐสภาประกอบกับการนำเสนอแนวคิดที่ว่าด้วยพฤติกรรมเลียนแบบด้านการใช้ความรุนแรงในสภา รวมทั้งการนำเสนอลงลึกโดยการนำทัศนะของ ฌาคส์ ร็องซิแยร์ ที่ว่าด้วยแนวคิดเรื่องการไม่เห็นด้วย โดยนำแนวคิดนี้มาวิเคราะห์ร่วมกับหลักการสำคัญของประชาธิปไตยและปรากฏการณ์การใช้ความรุนแรงในสภา และในท้ายที่สุด ได้นำเสนอแนวทางเบื้องต้นสำหรับการแก้ไขปัญหาพฤติกรรมการใช้ความรุนแรงในสภาประกอบไว้ด้วย อย่างไรก็ดี ผลที่ได้รับจากการวิเคราะห์และสังเคราะห์องค์ความรู้ดังกล่าวข้างต้นนี้ สามารถกล่าวได้ว่า การใช้ความรุนแรงในสภาจะไม่เกิดขึ้น หากทุกฝ่ายยึดมั่นในหลักการของประชาธิปไตยอย่างเข้มงวด โดยเฉพาะหลักการที่ว่าด้วยนิติรัฐ หลักเหตุผล หลักการปกครองของเสียงส่วนใหญ่โดยไม่ลืมเสียงส่วนน้อย และที่สำคัญที่สุดก็คือ การทำให้ประชาธิปไตยเป็นระบอบการปกครองของคนส่วนใหญ่ ที่ดำเนินไปเพื่อผลประโยชน์ของคนทั้งหมด Democracy and Imitative Behavior of Using Violence in the House of Parliament The phenomenon of using violence in the house of parliament on many countries around the world including Thailand could be seen on one aspect as imitative behavior of using violence. Thus, this article had an objective to review some meanings and principles of democracy, especially, of the parliamentary system. Moreover, it presented the concept of imitative behavior of using violence in the house of parliament. Furthermore, it went in depth on the vision of Jacques Ranciere that talked about the concept of disagreement using this concept to analyze with the democratic principles and the phenomenon of using violence in the house of parliament. Finally, it talked about the basic way for solving the behavior of using violence in the house of parliament all together. However, summarizing that came from the process of analyzing and synthesizing on some knowledge above could be said that there was no using violence in the house of parliament if everybody would respect strictly on the democratic principles especially on the principle of rule of law, rationality, majority rule and minority right. And the most important was making democracy being the regime that ruled by the many but for everybody’s benefit.